PROTEKSI OVERHEAT PADA PENGENDALI MOTOR BRUSHLESS DIRECT CURRENT UNTUK BECAK LISTRIK DENGAN SENSOR SUHU MENGGUNAKAN XMC1302 - Trisna Pambudi, Kukuh; Firmansyah, Eka; Dhiya’ulhaq Priambodo, Muhammad Dyffa; Muhammad, Fadel (Universitas Lampung, 2026)
BLDC motor controllers in light electric vehicles such as electric pedicabs are prone to excessive temperature rise due to high current and continuous operation, which may reduce system reliability. This study implements a BLDC motor controller based on the Infineon XMC1302 microcontroller using a Hall-sensor-based block commutation method and an NTC thermistor for thermal protection. Temperature data are acquired through the integrated ADC and used to adaptively regulate the PWM duty cycle via a throttle derating mechanism. Experimental results show that the duty cycle starts to decrease when the temperature exceeds 50 °C and is completely disabled above 70 °C. Laboratory and field tests on an electric pedicab demonstrate a continuous reduction in the speed profile as temperature increases, confirming effective thermal protection performance.